Nutrient rich karanja (Pongamia pinnata L.) Pierre genotypes for diversified uses : An inventory: NUTRIENT RICH KARANJA GENOTYPES FOR DIVERSIFIED USES - I Y L N MURTHY; N MUKTA (Journal of Oilseeds Research, 2013)
A study was conducted to quantify the content of major nutrients nitrogen (N), phosphorus (P) and potassium (K) in recently matured leaves (RML) of 66 genotypes of Pongamia pinnata (L) Pierre, which were grown under same soil fertility and management conditions at the Rajendranagar Research Farm of the Directorate of Oilseeds Research, Hyderabad. Classification of the accessions on the basis of their nutrient content indicted that majority of the genotypes have medium N, P and K content in the RML while two genotypes viz., DORPP 27 and 67 recorded high N content. Present investigation indicates that leaves of P. pinnata genotypes, DORPP 27 and 67 have shown better nutrient composition to use as manure as well asfeed. Further, the index developed may be useful in assessing the nutrient status of recently matured leaves for deficiency, sufficiency and toxicity in various crops.